The Influence of Greenpeace.Id Social Advertising on Green Attitude - Widodarjo, Aditya; Putri, Sekartaji Anisa (International Journal of Environmental Communication (ENVICOMM), 2023)
This study aims to determine how much influence greenpeace social advertising has on green attitude. Greenpeace is one of the Non-Governmental Organization (NGO) known for its efforts in promoting environmental awareness and nature protection. In the digital era, Greenpeace also uses social advertising to deliver environmental messages to a wider audience. This research uses a quantitative approach with a survey method to respondents who have seen advertisements from Greenpeace. Data will be collected through a questionnaire designed to measure the effect of social advertising on green attitude. The research is an explanatory type quantitative study with a positivist approach. The population used is a total of 30 million Intagram users and the sample uses a non-probability sampling method of purposive sampling with the Slovin formula with an error rate of 10%. The questionnaire was distributed to 100 respondents via google form and processed using SPSS version 29. Furthermore, the data was analyzed through simple linear regression test and coefficient of determination (R Square) test. The results of this study indicate that there is an influence of social advertising has an influence of 63.6% on travel interest and the rest is influenced by other factors outside the study. The hypothesis can be interpreted that Ha is rejected and Ha is accepted.